Penerapan Konseling Individu dengan Pendekatan Humanistik dalam Mengatasi Insecure pada Korban Bullying - Pratiwi, Vira; Razzaq, Abdur; Ramadoni, Muhamad Afdoli (Prodi Bimbingan Konseling FKIP UNDANA, 2023)
Insecure is a condition where individuals feel insecure, unsure, afraid, anxious, and so on. This study aims to know the description of insecure victims of bullying client